PERKEMBANGAN CABANG MUHAMMADIYAH METRO TIMUR DALAM BIDANG DAKWAH PENDIDIKAN DAN KESEHATAN TAHUN 2006-2019 - Lailatul Afifah; Ragil Agustono; Sumiyatun Sumiyatun (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The research objectives to be achieved are: 1) To analyze the development of the Muhammadiyah branch in the field of da'wah education 2006-2019. 2) To analyze the development of the Muhammadiyah branch in the field of Health da'wah 2006-2019. This research method is descriptive qualitative, data and data sources obtained from books in accordance with research studies, and Muhammadiyah figures as resource persons. Data collection techniques, namely literature study, observation, interviews and documentation. The validity of the data was carried out in stages of trustworthiness, transferability, certainty and accountability. Muhammadiyah is a large Islamic organization in Indonesia. The name of this organization is taken from the name of the Prophet Muhammad SAW, who was born 18 November 1912.The main objective of Muhammadiyah is to restore all irregularities that occur in the dakwah process. Muhammadiyah's charitable efforts in the field of da'wah are various, one of which is education and health preaching. Charity business in the field of education da'wah is one of the business deeds in Muhammadiyah whose movement is Islamic da'wah which is based on the values of charity ordered by Allah SWT.This form of charity business in the field of education is to establish schools from kindergarten to university level. The next charity business in the health sector established a health center to help the misery of the people at that time, because charities were created in the health sector.Keywords: Muhammadiyah, educational da'wah, health da’wah